Investigating Supported or Unsupported Individual and Group Work in Open Forums in an Open Educational Resources Repository - Wilson, Tina (Proceedings of the International Conference on Networked Learning, 2008)
The availability of networked lifelong learning opportunities is becoming more important as parts of the world come to terms with the reality of an aging society. Lifelong learning needs to be actively supported through easy access to online educational resources. Once access to Open Educational Resources (OERs) is achieved, how will those teaching different age groups facilitate the learning experience? This paper investigates how an Open Educational Resources Repository could facilitate online activity between learners and teachers who are used to a closed (password protected) online environment. The eleven participants (from ten institutions) involved in this research are based internationally and their learners range from school age to later-life learners. The idea of sharing content is not new. MIT’s course materials have been available to the world through its Open CourseWare (OCW) initiative since September 2002. Today’s entrants to this arena provide an environment, which includes complementary social networking tools. One of these new OER initiatives is from the United Kingdom (UK) Open University and is called OpenLearn. What is novel about OpenLearn is the availability of distance learning OERs themselves and complementary social networking tools. This initiative is funded by the William and Flora Hewlett Foundation and was launched on 25th October 2006. One of OpenLearn’s social networking tools is an open online forum attached to each ‘unit’ of Open Educational Resource. This paper focuses on the facilitators’ perspective of how they would use OERs and forums with their learners in terms of: Supported and unsupported access, Individual or group work, Usage of an open forum or the institutions own communications facility. The discussion based on interviews is also supported by a short case study provided by the later-life learning organisation involved in this study. Enthusiasm to adopt the OpenLearn units appears apparent with all participants eager for their learners to use the OpenLearn units in either a supported or unsupported way. The majority are also enthusiastic for their learners to work both individually and in groups around the OpenLearn units. Most participants were also in support of using the OpenLearn unit forum for group discussion. These results form a basis for more detailed research into the best ways to support communities of learners to collaborate and cooperate in an OER environment. Future work will investigate forum usage within the IT and Computing Topic area. Please refer to the full paper for more information.